EFFECTIVE TOURISM MANAGEMENT AS A GUARANTEE OF SUSTAINABLE ECONOMIC DEVELOPMENT OF THE UNITED TERRITORIAL COMMUNITIES OF PRICARPATHIA - Sheketa , E. Yu.; Kaziuka , N.P. (The actual problems of regional economy development, 2021)
The article examines the features of reforming the system of local self-government of decentralization of power. The basic normative-legal legislation of Ukraine, which regulates the reform of decentralization is analyzed. An indisputable step in decentralization reform is the voluntary creation of independent administrative-territorial units – united territorial communities, whose success lies in the realization that power is concentrated in the hands of everyone, and it is the community that determines the priorities of its development and budget spending. A SWOT-analysis of the tourist services market in Prykarpathia region is carried out; in particular, weaknesses and strengths, opportunities for expansion and restraining factors of development of the sphere of tourist industry in the region were identified. The article stipulates that the ecological orientation of all sectors of the region's economy should become an important reference point of UTC, as care for the environment is the key to harmonious human coexistence in society and the main prerequisite for sustainable development and maximum preservation of all living things for future generations. The article establishes that effective management and awareness of UTC that the tourism industry has every chance to become one of the most profitable sectors of the region, allows overcoming the negative trends in the tourism market by forming a specific action plan through the implementation of state and regional programs in tourism. Thanks to the thought-over information and marketing support, it is possible to form a qualitative competitive tourist product in the world market. The goals of sustainable development of Ukraine are a reference point for the development of projects, forecasts and regulations for the effective economic, environmental and social areas of sustainable development of each newly created UTC. The analysis the advantages and disadvantages for the development of the tourism industry in Prykarpattia shows, that UTC should focus on the development of infrastructure in the region: repair of roads, expanding air travel, improving the quality, safety and comfort of land transport, for the safety of tourists. An important guideline of UTC should be the ecological orientation of all sectors of the region's economy, such as care for the environment is the key to harmonious human coexistence in society and the main prerequisite for sustainable development and maximum preservation of all living things for future generations.